Severity of Malocclusion and Orthodontic Treatment Needs among 12- to 15-Year-Old School Children of Davangere District, Karnataka, India - Shivakumar, KM; Chandu, GN; Shafiulla, MD (European Journal of Dentistry, 2010)
Objectives: To assess the severity of malocclusion and orthodontic treatment needs among 12- to 15-year-old school children of Davangere District, India, by using the Dental Aesthetic Index (DAI).Methods: A descriptive cross-sectional study was conducted among 1800 12- to 15-year-old school children of Davangere District, Karnataka, India. Talukas (administrative units in some states in India) were considered clusters. Schools were selected using simple random sampling procedures. The 300 study subjects were selected using systematic random sampling procedures. Data consisting of DAI components were recorded pro forma. The collected data were subjected to statistical analysis. The Chi-square test (X2) was used to compare malocclusion severity. The analysis of variance (ANOVA) test was used to compare the changes in DAI scores and the mean DAI scores between age groups. The Z test was used to compare mean DAI scores between the 2 sexes and between children residing in urban and rural areas.Results: Of the 1800 school children examined, 899 (49.9%) were boys and 901 (50.1%) were girls. Most of the children (79.9%) had DAI scores ≤ 25 with no or minor malocclusion requiring no or little treatment, 15.4% had DAI scores of 26–30 with definite malocclusion requiring elective treatment, 4.2% had DAI scores of 31–35 with severe malocclusion requiring highly desirable treatment, and 0.5% had DAI scores ≥ 36 with handicapping malocclusion requiring mandatory treatment.Conclusions: The majority of the children in our study (79.9%) required no or little treatment; 20.1% had definite malocclusion requiring definite orthodontic treatment. (Eur J Dent 2010;4:298- 307)
Keywords: Malocclusion; Dental Aesthetic Index; Treatment needs